Political Refugee and Translation - Fernández Rodríguez, Áurea (Madrygal. Revista de Estudios Gallegos, 2017)
The general objective of this study is to highlight the specificity of the exile of Galicians from the point of view of translation as a practice. The article refers to the activity of some Galician translators, mostly graduates, writers and humanists, who took on the duty of striving to maintain and recover the cultural progress of the Republican Spain that existed prior to the Spanish Civil War. These intellectuals simultaneously introduced new texts that boosted the cultural and publishing industry in the host countries. As an example, the paper describes the activity of the political refugee and historian José Almoina de Mateos (1903-1960).
Keywords: Translation; Political Refugee; Galician Culture; Publishing House; Argentina; Mexico.